Principles of Accounting/Financial Accounting: An Introduction (Book). - Hendrickson, Harvey S.; Madison, Roland L.; Fleischman, Richard K. (The Accounting Review, 1986)
Reviews two books. "Principles of Accounting," 3rd ed., by Paul H. Walgenbach, Norman E. Dittrich and Ernest I. Hanson; "Financial Accounting: An Introduction," 4th ed., by Paul H. Walgenbach, Ernest I. Hanson and Norman E. Dittrich.